Penguatan UKM Produk Eksport Berbasis Bahan Baku Lokal Melalui Strategi Peningkatan Kualitas Produk dan Pengelolaan Manajemen - Sarwono, Aris Eddy (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2021)
This activity is carried out at SMEs made from sheepskin which produce calligraphy ornaments with a market share of 95% in the Middle East. The location of the activity was carried out in Sukoharjo Regency, Central Java. The purpose of this activity is to improve the quality of the products produced and improve the quality of their management. The results of the activities carried out to improve quality are by improving the storage method, the process of managing raw leather and the drying process, while for the management process, the resulting activities are improving managerial and simple bookkeeping for UKM Partners.